Manuscripts and their (proof-)texts: Paradigms for purity and holiness in the Community Rule and the Damascus Document - Quick, L (Verlag Herder GmbH, 2017)
This paper considers the scriptural paradigms favoured by the Community Rule and the Damascus Document, as a new way to understand the differing presentations of purity and holiness in each text. By demonstrating that the Community Rule promotes the Priestly source in matters of theology and cult, while the Damascus Document prefers the book of Deuteronomy, it is proposed that the differing conceptions of purity and holiness in the Priestly and Deuteronomic Schools has generated a similar distinction in these documents from Qumran.